KONSINYASI GANTI RUGI DALAM PENGADAAN TANAH UNTUK KEPENTINGAN UMUM TERKAIT ADANYA SENGKETA KEPEMILIKAN - Kustiani, Larasati; Slamet, Sri Redjeki; Olivia, Fitria; Arianto, Henry (Lex Jurnalica, 2025)
AbstractLand acquisition is a government action to obtain land for various development purposes by providing compensation, which is deposited in the District Court. This research examines the disbursement of compensation consignment for land acquisition in the event of land ownership disputes and the legal protection for landowners in the presence of ownership disputes over the consigned compensation. the method of normative legal research through document studies on land acquisition for public interest and analyzed qualitatively. In the event of a land ownership dispute, for the disbursement of compensation consignment, the disputing parties must file a lawsuit to determine who is entitled to receive the compensation or through a settlement effort with mediation. The entitled party must receive legal protection, which includes preventive protection. The government must ensure land ownership affected by land acquisition before the establishment of the normative field and ensure that the disputing parties comply with the court's decision as the basis for the disbursement of the consignment. As for repressive protection, the consignment cannot be disbursed without a court ruling that determines the entitled party to the land. Keywords: consignment, land acquisition, ownership dispute